Computational intelligence concepts to implementations - Eberhart, Russell C. (Elsevier/Morgan Kaufmann Publishers, 2007)
Explores a number of key themes, including self-organization, complex adaptive systems, and emergent computation. This title details the metrics and analytical tools needed to assess the performance of computational intelligence tools. It concludes with a series of case studies that illustrate a range of successful applications.
Includes bibliographical references (pages 439-453) and index. - Print version record
Keywords: Computational intelligence; Neural networks (Neurobiology); Intelligence informatique; Réseaux neuronaux (Neurobiologie); COMPUTERS; Enterprise Applications; Business Intelligence Tools; COMPUTERS; Intelligence (AI) & Semantics; dissertations; Academic theses; Thèses et écrits académiques